Rethinking childhood: child and space (Morepress Books, 2024)
Contemporary (postmodern) reassessments of children and childhood have significantly altered and modified the perception of childhood in general, partly by moving away from understanding childhood solely as a developmental stage. Instead, the contemporary perspectives approache the conception of childhood as a social construct that is dependent on time, place, and culture. Correspondingly, the representation of the child has transformed from that of a passive entity in need of physical and emotional protection to an active social agent who seeks to engage actively with their surroundings. This shift in the educational paradigm and the perception of the child and childhood has led social and human sciences to find a shared interest in an interdisciplinary dialogue that best interprets, illuminates, and conceptualizes childhood. Recent literature explores childhood from an angle of exceptional scientific complexity, while still prioritizing multidisciplinary scientific and epistemological approaches. This is the central theme of the series of publications titled “Rethinking Childhood,” which comes as a result of the collaboration between two higher education institutions: the Department of Teacher and Preschool Teacher Education at the University of Zadar and the Faculty of Education at the University of Maribor. The monographs aim to position themselves within the broader context of contemporary childhood studies, bringing together experts from various fields and cultures who examine childhood from different perspectives. This scientific monograph explores the interrelationships between two concepts: childhood and space. It focuses on the influence of the child on space and, conversely, the influence of space on the child and childhood. The significance of space and spatiality can be recognized across various scientific disciplines, including pedagogy, psychology, sociology, philology, philosophy, history, anthropology, cultural studies, and childhood studies, as well as within the arts. By rethinking spatial categories and linking them with the concepts of child and childhood in scientific discussions, we find intriguing insights into the phenomena of space and spatiality – ranging from real (physical) spaces to the mental and emotional spaces of the child, and extending to the constructed (social) spaces of childhood. It is crucial to highlight that the concepts of space associated with the child and childhood are viewed as cultural constructs specific to a particular time. Scientific monograph consists of 27 scientific papers, including 16 original research papers, 9 pilot study papers (preliminary communications), and 2 review papers. The papers are divided into four thematic sections: Interpretative Potentials of Space in the Context of Literature and Culture; Spatial Meanings in Language and Film; Spiritual, Virtual, and Real Spaces in Education; and Spaces in Play and Art. Each section focuses on specific scientific disciplines, where researchers of similar profiles engage in reasoned discourse, structuring a multidisciplinary and holistic approach to childhood spatiality, while providing an engaging perspective on the relationship between children (childhood) and space. All papers underwent individual double-blind peer-review process, which involved reviewers from various domestic and international higher education institutions (a total of 68 reviewers), the monograph has been reviewed in its entirety.